Audio-visual temporal perception in children with restored hearing. (May 2017) - Gori, Monica; Chilosi, Anna; Forli, Francesca; Burr, David
Abstract: It is not clear how audio-visual temporal perception develops in children with restored hearing. In this study we measured temporal discrimination thresholds with an audio-visual temporal bisection task in 9 deaf children with restored audition, and 22 typically hearing children. In typically hearing children, audition was more precise than vision, with no gain in multisensory conditions (as previously reported in Gori et al. (2012b)). However, deaf children with restored audition showed similar thresholds for audio and visual thresholds and some evidence of gain in audio-visual temporal multisensory conditions. Interestingly, we found a strong correlation between auditory weighting of multisensory signals and quality of language: patients who gave more weight to audition had better language skills. Similarly, auditory thresholds for the temporal bisection task were also a good predictor of language skills. This result supports the idea that the temporal auditory processing is associated with language development. Highlights: Deaf children with restored hearing show higher Audio and visual thresholds than typical children. Deaf children with restored audition show stronger multisensory gain. Language abilities are better in children with hearing restored who gave more weight to audition. We discuss the association between temporal processing and language development.